Dampak Kebijakan Zonasi Sekolah Menengah atas di Jakarta Barat terhadap Kualitas dan Pemerataan Pendidikan Menengah - Siagian, Siagian; Baginda Edward; Murniarti, Murniarti; Erni, Erni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the impact of the Senior High School (SMA) zoning policy in West Jakarta on the quality and equity of secondary education, particularly in terms of equitable access, quality of educational services, and implementation challenges at the school level. The research method used is a qualitative approach with a literature review through policy document analysis and a systematic synthesis of relevant scientific journals, analyzed using Qualitative Content Analysis and Theoretical Comparative Synthesis techniques. The results show that the zoning policy has succeeded in achieving equal access to education structurally through student redistribution and reducing the polarization between favorite and non-favorite schools. However, it has not succeeded in achieving equal quality functionally due to the ongoing unequal distribution of qualified teachers, disparities in facilities, and pedagogical unpreparedness in dealing with student heterogeneity. This condition has created a crisis in the learning process, particularly in the implementation of learning differentiation and meeting the needs of the Minimum Competency Assessment (AKM). The conclusion of this study confirms that an effective zoning policy is a demand-side policy, but it remains weak in strengthening the supply-side policy related to human resource capacity and the quality of the learning process. Therefore, affirmative interventions are needed to redistribute teachers, improve pedagogical competence, and strengthen education quality governance. Keywords: Zoning Policy, Education Equity, Education Quality, Quality Teachers